EFFECT OF CHRONIC EXPOSURE OF SPECKLED PRAWN, METAPENAEUS MONOCEROS (FABRICIUS) TO NAPHTHALENE - Deshmukh, Nandini V; Masurekar, Vasant B (Indian Journal of Fisheries, 2011)
Naphthalene, the most toxic constituent of petroleum hydrocarbon was selected as a pollutant tostudy the effects on survival of speckled prawn, Metapenaeus monoceros which is one of the commerciallyimportant species of edible prawns. The prawns were exposed to different concentrations of naphthaleneby employing static bioassay procedure for 1 to 8 week period. Adverse effects on survival in M. monoceroswere found to be directly related to the concentration of naphthalene used. Mortality rates thusobtained served as index of the effects of chronic exposure to different naphthalene concentrations on thesurvival of the animals.